The interaction of hepatitis A virus (HAV) with soluble forms of its cellular receptor 1 (HAVCR1) share the physiological requirements of infectivity in cell culture - Silberstein, Erica (BioMed Central, 2009)
BACKGROUND: Hepatitis A virus (HAV), an atypical Picornaviridae that causes acute hepatitis in humans, usurps the HAV cellular receptor 1 (HAVCR1) to infect cells. HAVCR1 is a class 1 integral membrane glycoprotein that contains two extracellular domains: a virus-binding immunoglobulin-like (IgV) domain and a mucin-like domain that extends the IgV from the cell membrane. Soluble forms of HAVCR1 bind, alter, and neutralize cell culture-adapted HAV, which is attenuated for humans. However, the requirements of the HAV-HAVCR1 interaction have not been fully characterized, and it has not been determined whether HAVCR1 also serves as a receptor for wild-type (wt) HAV. Here, we used HAV soluble receptor neutralization and alteration assays to study the requirements of the HAV-HAVCR1 interaction and to determine whether HAVCR1 is also a receptor for wt HAV. RESULTS: Treatment of HAV with a soluble form of HAVCR1 that contained the IgV and two-thirds of the mucin domain fused to the Fc fragment of human IgG1 (D1 muc-Fc), altered particles at 37°C but left a residual level of unaltered particles at 4°C. The kinetics of neutralization of HAV by D1 muc-Fc was faster at 37°C than at 4°C. Alteration of HAV particles by D1 muc-Fc required Ca, which could not be replaced by Li, Na, Mg, Mn, or Zn. Neutralization of HAV by D1 muc-Fc occurred at pH 5 to 8 but was more efficient at pH 6 to 7. D1 muc-Fc neutralized wt HAV as determined by a cell culture system that allows the growth of wt HAV. CONCLUSION: The interaction of HAV with soluble forms of HAVCR1 shares the temperature, Ca, and pH requirements for infectivity in cell culture and therefore mimics the cell entry process of HAV. Since soluble forms of HAVCR1 also neutralized wt HAV, this receptor may play a significant role in pathogenesis of HAV.